Dilation velocity is associated with Glasgow Coma Scale scores in patients with brain injury. (5th January 2021) - Thakur, Barsha; Nadim, Hend; Atem, Folefac; Stutzman, Sonja E.; Olson, DaiWai M.
ABSTRACT: Background : Pupillary light reflex (PLR) is informative about patients with neurological injury. Automated pupillometry provides discrete variables such as dilation velocity (DV). The objective of this study is to determine association between DV and Glasgow Coma Score (GCS), for patients with acquired brain injury. Methods : There were 2, 208 patients with acquired brain injury, pupillometer readings, and daily GCS values available in our registry. GCS was trichotomized as severe (GCS ≤ 8), moderate (GCS = 9–12), or mild injury (GCS = 13–15). Generalized Linear Mixed Model regression was used to identify correlation between DV and GCS. Results : Patient mean age was 58.9 years, and 49.11% were female. There were 42, 229 observations of GCS and DV. Mean admission GCS was 11.7. In the left eye, there was a statistically significant negative association for mean DV in patients with mild (DV = 0.85 mm/s), moderate (DV = 0.71 mm/s), and severe (DV = 0.48 mm/s) injury ( p < .0001). Similar results were noted in the right eye with mild (DV = 0.87 mm/s), moderate (DV = 0.72 mm/s), and severe (DV = 0.50 mm/s) injury ( p < .0001). Conclusion : Higher GCS is associated with faster DV. PLR may provide a biomarker of injury when a neurological exam is limited. Trial Registration : NCT02804438 (June 17, 2016). ABBREVIATIONS : GCS: Glasgow Coma Scale; PLR: Pupillary Light Reflex; DV: Dilation velocity; ICP: Intracranial pressure; NPi: Neurological pupil index; mRS: Modified Rankin Score; PCT: Percent change in size (pre and post constriction); Lat: Latency; CV: Constriction velocity; GLMM: Generalized Linear Mixed Model